2015
DOI: 10.1111/2041-210x.12467
|View full text |Cite
|
Sign up to set email alerts
|

Use of ddPCR in experimental evolution studies

Abstract: 1. Experimental evolution is an important research framework for evolutionary biologists as it allows direct testing of fundamental theories about adaptation and diversity, which often requires the tracking of genotypes or alleles over time. This however requires tools such as genetic markers, distinguishable morphological characters or genotyping, which can be time and labor intensive, and especially if high-throughput processing is necessary. 2. Here we present a novel approach of combining multiplex ddPCR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
(61 reference statements)
2
17
0
Order By: Relevance
“…After optimisation of the ddPCR conditions, our assay proved to be very sensitive to measuring FA of MUT/WT alleles in faecal larval cultures from infected sheep, irrespective of the DNA concentrations (0.1–132.5 ng/μL). This is basically in agreement with findings in other studies quantifying the frequencies of rare alleles ( Taylor et al, 2015 ; Koch et al, 2016 ; Uchiyama et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…After optimisation of the ddPCR conditions, our assay proved to be very sensitive to measuring FA of MUT/WT alleles in faecal larval cultures from infected sheep, irrespective of the DNA concentrations (0.1–132.5 ng/μL). This is basically in agreement with findings in other studies quantifying the frequencies of rare alleles ( Taylor et al, 2015 ; Koch et al, 2016 ; Uchiyama et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…In channel 2, where fluorescence is emitted with the help of the MT probe carrying a HEX™ fluorescence-producing molecule, a second band is seen at ∼4000 AU. Koch et al (2016) observed a similar occurrence of the second band in channel 2 and concluded that it was likely due to the lower efficacy with which secondary dyes, such as HEX™ and VIC ® are detected. However, upon further discussion with BioRad technicians, it was suggested that these lower-specificity bands represent amplified DNA being bound to by the wrong probe (i.e.…”
Section: Discussionmentioning
confidence: 80%
“…On the other hand, QPCR is advantageous when comparing more than two organisms because the currently available BioRad DDPCR system can only multiplex two fluorescent dyes (Koch et al . ). DDPCR is often, but not always, both more sensitive and more expensive per sample than QPCR (Kim et al .…”
Section: Discussionmentioning
confidence: 97%
“…DDPCR is also advantageous in assays of unculturable organisms because it does not require a standard curve of DNA quantity to cycle threshold. On the other hand, QPCR is advantageous when comparing more than two organisms because the currently available BioRad DDPCR system can only multiplex two fluorescent dyes (Koch et al 2016). DDPCR is often, but not always, both more sensitive and more expensive per sample than QPCR (Kim et al 2014;Nathan et al 2014;Yang et al 2014).…”
Section: Recommendations For Future Researchersmentioning
confidence: 99%